The technical level and efficiency of blister machines - Buzlukova, Olga; Senin, Oleksandr; Gubenia, Oleksii; Guts, Viktor (My University, 2014)
The proposed evaluation method allows to predict the change of qualities products in time, rational to choice turnaround cycle of equipment, to reduce operating costs for service, to control of finished products. Пропонований метод оцінки дозволяє прогнозувати зміну якостей продуктів в часі, раціональних, щоб вибір оборотного циклу устаткування, знизити експлуатаційні витрати на обслуговування, контролювати готової продукції.
Keywords: блістерна машина; технічний рівень; ефективність; technical level; blister machine; effectiveness; кафедра екології та екоменеджменту; кафедра машин і апаратів харчових та фармацевтичних виробництв